Access control systems security, identity management and trust models - Benantar, Messaoud (Springer Science+Business Media, 2006)
"Access Control Systems: Security, Identity Management and Trust Models provides a thorough introduction to the foundations of programming systems security, delving into identity management, trust models, and the theory behind access control models. The book details access control mechanisms that are emerging with the latest Internet programming technologies, and explores all models employed and how they work. The latest role-based access control (RBAC) standard is also highlighted. This unique technical reference is designed for security software developers and other security professionals as a resource for setting scopes of implementations with respect to the formal models of access control systems. This book is also suitable for advanced-level students in security programming and system design."--Book jacket.